A man-made divide: Investigating the effect of urban–rural household registration and subjective social status on mental health mediated by loneliness among a large sample of university students in China - Yu, Hui; Xu, Shicun; Li, Hui; Wang, Xiaofeng; Sun, Qian; Wang, Yuanyuan (Frontiers in Psychology, 2022)
Introduction The urban–rural household registration system in China has been documented with profound social consequences in almost all areas of people’s life. This study aims to investigate the underlying mechanism of the rural and urban discrepancies on mental health conditions among a large sample of college students in China. Methods A survey was distributed among college students in China. A total of 96,218 college students from 63 colleges completed the survey, answering questions on their urban–rural household registration, disposable household income, subjective social status, feelings of loneliness, and anxiety and depression symptoms. Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) analyses were conducted, testing the effect of urban–rural registration on one’s mental health, mediated by subjective social status, and loneliness. Results Structural Equation Modelling (SEM) results revealed that the urban–rural household registration showed a direct effect on anxiety (B = −0.03, 95% CI [−0.038, −0.022], β = −0.03, p < 0.001) and depression (B = −0.03, 95% CI [−0.035, −0.023], β = −0.03, p < 0.001), indicating that rural household registration had a negative association with anxiety and depression symptoms, albeit the standardised estimate being very small. The indirect path from the urban–rural registration mediated through subjective social status and loneliness to anxiety and depression was both significant, with B = 0.01, 95% CI [0.010, 0.010], β = 0.01, p < 0.001, and B = 0.01, 95% CI [0.0090, 0.0090], β = 0.01, p < 0.001, respectively. The results of the indirect paths demonstrated that students of the rural household registration reported higher anxiety and depression symptoms through a lower subjective social status and higher level of loneliness. Conclusion This study indicated that decreasing the disparity of social status and tackling loneliness is the key to improve the overall mental health of college students. The urban–rural household registration system may have a very small direct effect on the college students’ mental health; but students of urban registration enjoyed higher subjective social status, which had a clear protective effect against anxiety and depression symptoms.